Analysis of oral microbial dysbiosis associated with early childhood caries - Hui Zheng; Tengfei Xie; Shaokai Li; Xiaotong Qiao; Youguang Lu; Yan Feng (BMC, 2021)
Abstract Background "Core microbes" play a key role in the development of caries and lead to microbial disorders. Our goal was to detect the core microbes associated with the microbiota imbalance in early childhood caries (ECC). Methods Fifteen caries-free children and fifteen high-caries (DMFT ≥ 10) children aged 4-6 years old were recruited according to the diagnostic criteria of caries suggested by the WHO. The 16S rRNA genes from samples of plaque in saliva were amplified by PCR, and the PCR products were sequenced by the Illumina Miseq platform. The sequencing results were analyzed by professional software to determine the composition and structure of the saliva microorganisms. Results There were statistically significant differences between the groups regarding the relative abundance of Streptococcus mutans (Wilcoxon rank-sum test, P < 0.05). No significant difference was found between the groups regarding other species or functional genes. Conclusion S. mutans, together with other pathogens, may play a prominent role and act as "core microbes" in the occurrence and development of early childhood caries.